2017
DOI: 10.1002/aenm.201700977
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microstructure in Oxygen Induced Photodegradation of Methylammonium Lead Triiodide Perovskite Films

Abstract: photovoltaic technology, where lifetimes greater than 25 years are required. [2] Although the issue of device stability has attracted increased attention of the photovoltaic research community in the last two years, reports that systematically study the fundamental causes (e.g., heat, electrical stress, humidity, oxygen, (UV) light, chemical precursors, processing conditions, influence of film quality and morphology) and mechanisms limiting the material and device stability remain scarce. [2][3][4][5] While th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
216
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(226 citation statements)
references
References 64 publications
(156 reference statements)
8
216
2
Order By: Relevance
“…Specifically, the influence of oxygen and light on MAPbI 3 has attracted great attention recently, and the study on improving the stability of MAPbI 3 against photo‐oxidation is springing up . Zhang and Sit have reported a pathway for breaking of the local octahedral Pb–I structure and the formation of the PbO precursor .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the influence of oxygen and light on MAPbI 3 has attracted great attention recently, and the study on improving the stability of MAPbI 3 against photo‐oxidation is springing up . Zhang and Sit have reported a pathway for breaking of the local octahedral Pb–I structure and the formation of the PbO precursor .…”
Section: Introductionmentioning
confidence: 99%
“…It is found that heat destroys the perovskite film in a layer‐by‐layer pathway sequentially from the surface to bulk with a lattice transition, causing a dramatic loss in photovoltaic performance . Oxygen could act as a catalyst to prompt CH 3 NH 3 + disintegrating into CH 3 NH 2 and hydrogen under irradiation . The perovskite semiconductor is sensitive to atmospheric environment.…”
Section: Introductionmentioning
confidence: 99%
“…Inverted architecture perovskite solar cell means that in this architecture indium tin oxide (ITO) is the anode, whereas the metal contact constitutes the cathode. Devices with 3 c –H were compared to devices without a HBL and with the commonly used bathocuproine (BCP) . Summarizing the results of CV, UV/Vis spectroscopy, and the ultraviolet photoemission spectroscopy (UPS) measurements, the corresponding energy diagram is shown in Figure b.…”
Section: Resultsmentioning
confidence: 65%
“…PEDOT:PSS was spin coated on the cleaned ITO substrate with annealing at 150 °C for 15 min. Lead acetate trihydrate perovskite solution was spin coated onto PEDOT:PSS in a drybox (relative humidity <5 %) with drying for 5 min and annealing at 100 °C for 5 min . The prepared samples were transferred into a N 2 ‐filled glovebox.…”
Section: Methodsmentioning
confidence: 99%